Variations in volatile flavour compounds in Crataegi fructus roasting revealed by E-nose and HS-GC-MS - Fei, Chenghao; Xue, Qianqian; Li, Wenjing; Xu, Yan; Mou, Liyan; Li, Weidong; Lu, Tulin; Yin, Wu; Li, Lin; Yin, Fangzhou (Frontiers in Nutrition, 2023)
Crataegi fructus (CF) is an edible and medicinal functional food used worldwide that enhances digestion if consumed in the roasted form. The odour of CF, as a measure of processing degree during roasting, significantly changes. However, the changes remain unclear, but are worth exploring. Herein, the variations in volatile flavour compounds due to CF roasting were investigated using an electronic nose (E-nose) and headspace gas chromatography–mass spectrometry (HS-GC-MS). A total of 54 components were identified by GC-MS. Aldehydes, ketones, esters, and furans showed the most significant changes. The Maillard reaction, Strecker degradation, and fatty acid oxidation and degradation are the main reactions that occur during roasting. The results of grey relational analysis (GRA) showed that 25 volatile compounds were closely related to odour (r >0.9). Finally, 9 volatile components (relative odour activity value, ROAV ≥1) were confirmed as key substances causing odour changes. This study not only achieves the objectification of odour evaluation during food processing, but also verifies the applicability and similarity of the E-nose and HS-GC-MS.